AAGBI: Safer pre‐hospital anaesthesia 2017: Association of Anaesthetists of Great Britain and Ireland. (3rd January 2017) - Lockey, D. J.; Crewdson, K.; Davies, G.; Jenkins, B.; Klein, J.; Laird, C.; Mahoney, P. F.; Nolan, J.; Pountney, A.; Shinde, S.; Tighe, S.; Russell, M. Q.; et al.
Summary: Pre‐hospital emergency anaesthesia with oral tracheal intubation is the technique of choice for trauma patients who cannot maintain their airway or achieve adequate ventilation. It should be carried out as soon as safely possible, and performed to the same standards as in‐hospital emergency anaesthesia. It should only be conducted within organisations with comprehensive clinical governance arrangements. Techniques should be straightforward, reproducible, as simple as possible and supported by the use of checklists. Monitoring and equipment should meet in‐hospital anaesthesia standards. Practitioners need to be competent in the provision of in‐hospital emergency anaesthesia and have supervised pre‐hospital experience before carrying out pre‐hospital emergency anaesthesia. Training programmes allowing the safe delivery of pre‐hospital emergency anaesthesia by non‐physicians do not currently exist in the UK. Where pre‐hospital emergency anaesthesia skills are not available, oxygenation and ventilation should be maintained with the use of second‐generation supraglottic airways in patients without airway reflexes, or basic airway manoeuvres and basic airway adjuncts in patients with intact airway reflexes.